2010
DOI: 10.1002/mrm.22387
|View full text |Cite
|
Sign up to set email alerts
|

Multislice perfusion of the kidneys using parallel imaging: Image acquisition and analysis strategies

Abstract: Flow-sensitive alternating inversion recovery arterial spin labeling with parallel imaging acquisition is used to acquire single-shot, multislice perfusion maps of the kidney. A considerable problem for arterial spin labeling methods, which are based on sequential subtraction, is the movement of the kidneys due to respiratory motion between acquisitions. The effects of breathing strategy (free, respiratory-triggered and breath hold) are studied and the use of background suppression is investigated. The applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
126
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(135 citation statements)
references
References 26 publications
9
126
0
Order By: Relevance
“…The timing of background suppression pulses is adjusted such that by the time of readout excitation, the static tissues of a predetermined range of T1 will be close to zero, while the fl ow contrast between tag and control images is preserved. We currently do not include background suppression in these values were comparable with those in previous studies ( 10,11,25,26 ). However, we found that measurements obtained with ASL and DCE MR imaging lacked correlation ( r = 0.32, P = .25) and consistency (ICC = 0.03) in the medulla.…”
Section: Genitourinary Imaging: Renal Perfusion 3-t Mr Imagingsupporting
confidence: 86%
See 1 more Smart Citation
“…The timing of background suppression pulses is adjusted such that by the time of readout excitation, the static tissues of a predetermined range of T1 will be close to zero, while the fl ow contrast between tag and control images is preserved. We currently do not include background suppression in these values were comparable with those in previous studies ( 10,11,25,26 ). However, we found that measurements obtained with ASL and DCE MR imaging lacked correlation ( r = 0.32, P = .25) and consistency (ICC = 0.03) in the medulla.…”
Section: Genitourinary Imaging: Renal Perfusion 3-t Mr Imagingsupporting
confidence: 86%
“…In this regard, researchers ( 10 ) have suggested inclusion of respiratory gating to reduce motion-related degradation in image quality, data corruption, or both. While prospective gating prolongs examination time even in collaborative subjects and may become impractical in patients, retrospective gating entails extended measurement to collect enough images in the same phase of respiration.…”
Section: Genitourinary Imaging: Renal Perfusion 3-t Mr Imagingmentioning
confidence: 99%
“…For example, different strategies have been employed to circumvent the problem of renal respiratory motion, including breath-holding, respiratory gating, or post processing registration. Gardener and Francis [19] found no difference in perfusion measurements made with either breath-holding or free breathing, but found reduced perfusion when background suppression was used to improve image quality, showing that some variations in imaging approach cause differences in perfusion measurements. Our ASL technique resulted in a scan time of 15 min, and breath-holding time of 12 s, which was tolerated by all participants.…”
Section: Discussionmentioning
confidence: 99%
“…Singleslice ASL data acquisition, with a single slice acquired in a few hundred milliseconds, could significantly lead to label decay over the time course required to acquire a multislice data set. Alternatively, multislice kidney ASL data can be collected by repeating the single-slice acquisition procedure multiple times (8). Because ASL-fMRI remains challenging in RBF studies (2), animal models with invasive measurements of blood flow may be necessary for validation of this technique.…”
Section: Discussionmentioning
confidence: 99%